THE INFLUENCE OF THE QUALITY OF MEDICINE INFORMATION SERVICES ON PATIENT SATISFACTION IN PHARMACIES IN THE MUARA TEWEH CITY REGION - Erlina Nadia; Tyas S Nugraha; Herda Ariyani (LPPM - Universitas Muhammadiyah Banjarmasin, 2024)
Pharmacists have a significant role in providing drug information. The level of patient satisfaction when utilizing pharmacy services is a reflection of the quality of pharmaceutical services provided by the pharmacy, which includes interactions with patients, overall aspects of the pharmaceutical service system, administration, financial aspects and the performance of pharmaceutical personnel.The purpose of this study was to determine the effect of drug information services on quality and patient satisfaction at the MUARA TEWEH City Pharmacy. The type of research used was descriptive with a Cross-Sectional approach method. The sample used in this study amounted to 100 people. The sample technique used was purposive sampling. The instrument used was a questionnaire distributed to patients who visited the pharmacy. Data was tested with multiple regression analysis. It is known that the results of the level of patient satisfaction with the provision of drug information on tangibles 78.25 (Satisfied), reliability 79.3 (Satisfied), responsiveness 82.8 (Very Satisfied), assurance 81.7 (Very Satisfied), empathy 84.7 (Very Satisfied), with the average value of the level of patient satisfaction with the provision of drug information and the quality of drug information services in the tangible dimension, reliability, responsiveness, assurance and empathy, namely 81.35 (Very Satisfied), so that together they have a significant influence on patient satisfaction in the Muara Teweh area Pharmacy by 52.9% (F-test = 21.079, p value = 0.000). From this study it can be concluded that there is an effect of the quality of drug information services on patient satisfaction at the Muara Teweh City Pharmacy.